REPRESENTASI CITRA PEREMPUAN JAWA DALAM FILM PUTERI GUNUNG LEDANG KARYA SAW TEONG HIN - Ilhamsyah, Ade; Yazid, Tantri Puspita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The film as a work of art is often interpreted the results of copyrighted works of art that have the completeness of some of the elements of art to meet the needs of a spiritual nature . The position of women often appears as a symbol of subtlety , emotional , something that moved slowly , sometimes even stops . Women are so close to the idiom - phrases such adversity , oppression , even in the " concept " which have already been accepted by the majority of our society that they are "objects " rather than " subject " for men . The term gender itself is still much less understood and putting equal to the sex or gender.The method used in this research is the method of critical discourse . Data collection techniques in this study using the method of analysis, semiotics . The location of this research will be held in Pekanbaru , Riau . Subjects in this study is the film Puteri Gunung Ledang By Saw Theong Hin , while objects in the study in this research is the Java Image Women in film Puteri Gunung Ledang . For data analysis , researchers used a method of interactive analysis and Hubberman Miles . As for checking the validity of the data , researchers used triangulation data technique.The results showed that in the film the daughter of Gunung Ledang we could see the loyalty and obedience of a female Javan weak and powerless , who want to maintain loyalty , but all in vain . In the film 's daughter Gunung Ledang , women are placed or positioned as a Java object, because the sentences in this film are using the passive voice . Here, researchers get a masculine aura of femininity of the female figure of Java. If you notice, the woman of Java is indeed the most courageous woman to wander even alone . Retno Dumilah independence seems flowing also in the blood of the blood of most women of Java.Keyword : Representation, Woman, Film, Puteri Gunung Ledang.